A Broadband Laboratory Study of the Seismic Properties of Cracked and Fluid‐Saturated Synthetic Glass Media. Issue 5 (12th May 2018) - Li, Yang; David, Emmanuel C.; Nakagawa, Seiji; Kneafsey, Timothy J.; Schmitt, Douglas R.; Jackson, Ian
Abstract: For better understanding of frequency dependence (dispersion) of seismic wave velocities caused by stress‐induced fluid flow, broadband laboratory measurements were performed on a suite of synthetic glass media containing both equant pores and thermal cracks. Complementary forced oscillation, resonant bar, and ultrasonic techniques provided access to millihertz‐hertz frequencies, 1 kHz frequency, and 1 MHz frequency, respectively. The wave speeds or effective elastic moduli and associated dissipation were measured on samples under dry, argon‐ or nitrogen‐saturated, and water‐saturated conditions in sequence. The elastic moduli, in situ permeability, and crack porosity inferred from in situ X‐ray computed tomography all attest to strong pressure‐induced crack closure for differential (confining‐minus‐pore) pressures <30 MPa, consistent with zero‐pressure crack aspect ratios <4 × 10 −4 . The low permeabilities of these materials allow access to undrained conditions, even at subhertz frequencies. The ultrasonically measured elastic moduli reveal consistently higher shear and bulk moduli upon fluid saturation—diagnostic of the saturated‐isolated regime. For a glass rod specimen, containing cracks but no pores, saturated‐isolated conditions apparently persist to subhertz frequencies—requiring in situ aspect ratios (minimum/maximum dimension) <10 −5 . In marked contrast, the shear modulus measured at subhertz frequencies on a cracked glass bead specimen of 5% porosity, is insensitive to fluid saturation, consistent with the Biot‐Gassmann model for the saturated‐isobaric regime. The measured dispersion of the shear modulus approaches 10% over the millihertz‐megahertz frequency range for the cracked and fluid‐saturated media—implying that laboratory ultrasonic data should be used with care in the interpretation of field data. Key Points: Glass media containing thermal cracks of low aspect ratio are of low enough permeability to remain undrained even at subhertz frequencies Use of forced oscillation (subhertz), resonant bar (kilohertz), and ultrasonic (megahertz) methods exposes dispersive behavior of such fluid‐saturated media Ultrasonic methods consistently probe the saturated isolated regime, whereas low‐frequency methods can also access saturated isobaric conditions